The self-rating of the effects of alcohol questionnaire as a predictor of alcohol-related outcomes in 12-year-old subjects. - Schuckit MA; Smith TL; Trim RS; Heron J; Horwood J; Davis J; Hibbeln J (Alcohol & Alcoholism)
A low level of response (LR), or low sensitivity, to alcohol as established by alcohol challenges has been shown to predict future heavier drinking, alcohol-related problems and alcohol use disorders. To date, only one study has evaluated the predictive validity of a second measure of LR as determined by the Self-Report of the Effects of Alcohol (SRE) Questionnaire. The current analyses evaluate the ability of SRE scores as determined at age 12 to predict heavier drinking and alcohol-related problems 2 years later in a sample from the United Kingdom. Methods: The subjects were 156 boys (54.5%) and girls from the Avon Longitudinal Study of Parents and Children (ALSPAC) who had reported consuming one or more standard drinks by age 12 and who were followed up 2 years later. Results: The age 12 SRE scores correlated with the number of drinks per week, maximum drinks and the number of alcohol problems both at baseline and at age 14 follow-ups. In these evaluations, a larger number of drinks required for effects on the SRE (i.e. a lower LR per drink consumed) related to heavier intake and alcohol-related difficulties. Simultaneous entry multiple regression analyses revealed that the age 12 SRE score maintained a significant relationship with age 14 higher number of drinks per week and the number of alcohol problems even when the age 12 values for alcohol intake and problems were used as covariates. Conclusion: The SRE scores appear to have value in predicting future heavier drinking and alcohol problems in 12-year olds that go beyond the information offered by the earlier drinking pattern alone.